2021
DOI: 10.1053/j.ajkd.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Factors for Progression of Diabetic and Nondiabetic CKD: Findings From the Chronic Renal Insufficiency Cohort (CRIC) Study

Abstract: on behalf of the CRIC Study InvestigatorsRationale & Objective: Identification of novel risk factors for chronic kidney disease (CKD) progression may inform mechanistic investigations and improve identification of high-risk subgroups. The current study aimed to characterize CKD progression across levels of numerous risk factors and identify independent risk factors for CKD progression among those with and without diabetes.Study Design: The Chronic Renal Insufficiency Cohort (CRIC) Study is a prospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 42 publications
2
36
0
5
Order By: Relevance
“…It is an early sensitive biomarker for kidney injury. Urinary NGAL showed association with eGFR decline and kidney transplant in nondiabetic CRIC population (hazard ratio 1.6, 95% CI 1.1–2.3) [ 20 ], whereas the association was not significant in those with diabetes [ 20 ]. Urine NGAL was not a predictor of CKD progression in the SPRINT substudy [ 16 ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…It is an early sensitive biomarker for kidney injury. Urinary NGAL showed association with eGFR decline and kidney transplant in nondiabetic CRIC population (hazard ratio 1.6, 95% CI 1.1–2.3) [ 20 ], whereas the association was not significant in those with diabetes [ 20 ]. Urine NGAL was not a predictor of CKD progression in the SPRINT substudy [ 16 ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Consistently, our cohort study found that the best predictive cutoff value of urinary NGAL to creatine ratio (uNCR) for DKD diagnosis was 60.685 ng/mg, and T2DM patients with the increased level of uNCR had a higher risk of nephrotic-range proteinuria and worse renal outcome ( 82 ). Furthermore, a more recent report from the CRIC study conducted at seven US clinical centers provided solid evidence that higher urinary NGAL levels were not only strongly associated with cardiac markers, but were also linked to an approximately twofold or greater risk of CKD progression in patients with DM ( 10 ). It has been postulated that NGAL captures some of the variability in the rate of kidney function decline independently of albuminuria or other risk factors and reflects tubular injury and inflammation in the setting of DKD ( 10 , 85 ).…”
Section: Challenges and Progress In The Application Of Novel Tubular Biomarkersmentioning
confidence: 99%
“…Furthermore, a more recent report from the CRIC study conducted at seven US clinical centers provided solid evidence that higher urinary NGAL levels were not only strongly associated with cardiac markers, but were also linked to an approximately twofold or greater risk of CKD progression in patients with DM ( 10 ). It has been postulated that NGAL captures some of the variability in the rate of kidney function decline independently of albuminuria or other risk factors and reflects tubular injury and inflammation in the setting of DKD ( 10 , 85 ).…”
Section: Challenges and Progress In The Application Of Novel Tubular Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations